Commuter's Transport Mode Preferences and Social Network Effects in New Zealand. (1st January 2019) - Sheng, Mingyue; Sharp, Basil
This paper investigates commuters' travel demand preferences in New Zealand's largest city, Auckland, by choosing between public transport and private cars, using data from the nationwide household travel survey for the period of 2005/06 to 2008/09. A two-step spatial probit model is applied to analyse the impact of endogenous social network effects on public transport usage. The study supports the social network effects argument. Controlling for factors such as personal/household and trip characteristics, petrol prices and time-effects, commuters have a higher probability of using transit services if they are surrounded by other public transport users.